EVALUATION OF THE PHYSICOCHEMICAL PROPERTIES OF MORINGA LEAVES (Moringa oleifera) IN DIFFERENT PROCESSINGMETHODS: EVALUASI SIFAT FISIKOKIMIA DAUN KELOR (Moringa oleifera) PADA METODE PENGOLAHAN YANG BERBEDA - Baihaqi, Baihaqi; Aprita, Ika Rezvani; Asrul, Asrul (PT. ROCE WISDOM ACEH, 2025)
Moringa leaves (Moringa oleifera) are well known for their high nutritional value and extensive health benefits. However, processing methods can significantly affect the essential nutrients in moringa leaves, including moisture, ash, and vitamin C levels. This study aims to evaluate the effects of three processing methods—oven drying, blanching followed by drying, and boiling—on these parameters. The results showed that the moisture content of fresh moringa leaves, initially at 73.2%, significantly decreased after drying (6.91%) and blanching (14.23%), while boiling increased the moisture content to 85.06%. The ash content increased with processing, from 2.61% in fresh leaves to 9.02% after drying, 11% after blanching, and 11.8% after boiling. Vitamin C degradation occurred due to heating, with drying causing a drastic reduction from 32.31 mg/100 g to 8.7 mg/100 g. Blanching better-preserved vitamin C levels (30 mg/100 g), while boiling surprisingly increased the vitamin C content to 49.08 mg/100 g, possibly due to enhanced extraction of compounds from cellular structures into the water. In conclusion, processing methods significantly impact the nutritional quality of moringa leaves. Drying is effective in reducing moisture content for prolonged storage, whereas boiling and blanching better preserve vitamin C content. These findings provide crucial insights for the food and pharmaceutical industries in determining the optimal processing method to maintain the nutritional value of moringa leaves.